2021
DOI: 10.1111/hsc.13479
|View full text |Cite
|
Sign up to set email alerts
|

Professional preference for mental illness: The role of contact, empathy, and stigma in Spanish Social Work undergraduates

Abstract: The treatment of the mentally ill people is a challenge across the world, and different professionals, such as doctors, social workers, psychologists, or nurses, take care of this group. Nonetheless, mental health is not a vocational sector preferred by students and professionals of many of these careers. Research has proposed that professional preference for a patient group would be positively influenced by intergroup contact (quantity and quality) and empathy (perspective‐taking), and negatively associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 90 publications
(162 reference statements)
0
5
0
Order By: Relevance
“…When looking at the various stigma subscales side by side, our research only demonstrates that psychiatric trainees are stigmatized less when it comes to societal duty compared to other groups. Previous research has demonstrated that a stigma attached to social duty has a detrimental impact on empathy [ 17 ]. An integrated relationship model has been proposed: physicians who have more experience, more excellent patient-to-physician contact, and more empathy toward patients with mental disorders feel less uneasy around those patients, and as a result, they tend to reduce the social distance that separates them from those patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…When looking at the various stigma subscales side by side, our research only demonstrates that psychiatric trainees are stigmatized less when it comes to societal duty compared to other groups. Previous research has demonstrated that a stigma attached to social duty has a detrimental impact on empathy [ 17 ]. An integrated relationship model has been proposed: physicians who have more experience, more excellent patient-to-physician contact, and more empathy toward patients with mental disorders feel less uneasy around those patients, and as a result, they tend to reduce the social distance that separates them from those patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that stigma toward social responsibility negatively affects empathy ( 20 ). An integrated relationship model has been proposed: physicians with a better experience, more excellent patient-to-physician contact, and more empathy toward them feel less uneasy with patients with mental disorders; thus, they tend to reduce their social distance from them ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…When measured separately, research found that quality and quantity contact contribute differentially to describing attitudes, social distance, and intergroup anxiety (e.g., Voci and Hewstone, 2003 ; Vezzali and Capozza, 2011 ; Méndez Fernández et al, 2022 ). For example, quantity may be better related with implicit attitudes while quality is more strongly related to explicit attitudes (e.g., Tam et al, 2006 ; Prestwich et al, 2008 ; Kanamori et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%